Effect of RHAG variants identified in Chinese population on RHAG mRNA splicing in vitro - Shuangshuang JIA; Mingming SUN; Jizhi WEN; Ling WEI; Guangping LUO; Yanli JI (Zhongguo shuxue zazhi, 2023)
Objective To study the effect of RHAG variants identified in Chinese population on mRNA splicing by minigene splicing assay(MSA) in vitro. Methods The pSplicePOLR2G minigene expression plasmids were constructed for 10 RHAG mutations with relatively high distribution frequency in Chinese population near splicing sites or synonymous mutations by analyzing the RHAG gene data in the KMxD database. Then, the wild-type and mutant plasmids were transfected into HEK 293T cells, and RNA was extracted 48 hours after transfection. After reverse transcription, specific primers were used for PCR amplification, and then agarose gel electrophoresis and capillary electrophoresis were performed to determine whether the mutations will affect the normal splicing of exons. Results MSA in vitro showed that 2 mutations (c.158-5delT, c. 807+ 3A>C) near the splicing site reduced the amount of normal transcripts slightly. The remaining 8 synonymous mutations(c.312G>A, c. 341+ 3G>A, c. 609C>T, c. 681G>A, c. 861G>A, c. 957T>A, c. 984T>C and c. 1139-7G>A) had no impact on the splicing of RHAG mRNA. Conclusion This study showed that RHAG gene was conservative in terms of splicing, and the mutations near splicing sites and synonymous mutations were less likely to cause abnormal splicing of RHAG gene.